Initial management of acute medical patients : a guide for nurses and healthcare practitioners - Wood, Ian, 1962-; Garner, Michelle (Chichester, West Sussex : Wiley-Blackwell, 2012)
"Initial Management of Acute Medical Patients is a clinically focused, practical and contemporary guide for assessing and managing patients with acute medical conditions. Suitable for all nurses and healthcare practitioners in medical assessment units and medical wards, as well as A & E staff, it uses a structured approach based on common presenting features and focuses on the first 24 hours of the patient's hospital stay. It draws on a wide range of supporting evidence and also provides sources for further reading. Key features: Written predominantly by nurses for nurses, this text is also suitable for a range of healthcare professionals, including paramedics and nurse practitioners, and anybody working in an acute care environment, including primary care assessment units, clinical decision units and intermediate care Designed as a quick reference text for use in clinical practice Extensively referenced throughout, thus increasing its appeal to practitioners at all stages of their careers and to those who are undertaking further study Devotes two entire chapters to assessing and meeting the acute care needs of vulnerable adults (i.e. older adults, those with mental health needs, and those with learning disabilities), and discussing best practice in dealing with sudden death Each chapter offers clear, concise and down-to-earth information based on a common presenting symptom and provides practical advice, supported by best evidence and the most up to date clinical guidelines Fully updated and extensively expanded to include recent guidelines and procedures"--EBL.
Initial assessment of the acute medical patient -- Vulnerable groups -- Sudden death -- Cardiac arrest -- Shock -- Altered consciousness -- Shortness of breath -- Chest pain -- Abdominal pain and upper gastrointestinal bleeding -- Extremity pain and swelling.
Revised edition of: Medical assessment units / edited by Ian Wood and Michelle Rhodes. London : Whurr, 2003.
Includes bibliographical references and index.
Print version record.
Keywords: Critical care medicine -- Methods; Emergency nursing -- Methods; Nursing assessment -- Methods; Triage (Medicine) -- Methods; MEDICAL -- Critical Care; MEDICAL -- Nursing -- Critical & Intensive Care; Critical care medicine; Emergency nursing; Nursing assessment; Triage (Medicine); Critical Care -- methods; Emergency Nursing -- methods; Acute Disease -- nursing; Nursing Assessment -- methods; Triage -- methods; Electronic books; Methods (Music)